State, Society, and Displacement: The Social Integration of IDPs from North Waziristan in Bannu (Al-Qamar, 2025)
This paper explores the social integration of Internally Displaced Persons (IDPs) from North Waziristan in Bannu. It examines their adaptation to the host community, focusing on cultural compatibility, psychological adjustment, livelihood strategies, and social relations. Using qualitative methodology, in-depth interviews were conducted with affected households to gather detailed insights into their experiences and perceptions. Findings reveal significant cultural affinity between IDPs and locals, gradual psychological adaptation, and increasing economic self-reliance, despite initial challenges related to shelter, security, and social stigma. The research highlights factors facilitating integration and persistent barriers affecting the IDPs' long-term settlement
Keywords: Internally Displaced Persons; Social Integration; North Waziristan; Bannu; Cultural Adaptation; Psychological Adjustment; Livelihood; Displacement; Host Community; Migration